Book Review: The Politics of Islamic Law: Local Elites, Colonial Authority and the Making of the Muslim State by Iza R. Hussin - Hamzić, Vanja (London School of Economics, 2016)
In The Politics of Islamic Law: Local Elites, Colonial Authority and the Making of the Muslim State, Iza R. Hussin traces a riveting history of Islamic law as it encounters, and is inevitably transformed by, British colonialism in Malaya, Egypt and India. It is a work of unique critical sensibilities, setting the scene for future interdisciplinary research of colonial and postcolonial Islamic law as fruitful analytical categories, finds Vanja Hamzić.